Tax Avoidance on Institutional Ownership: Case Study of Banking Companies in Indonesian Capital Market - Reswita, Yefri; Lukman, Syukri; Febrianto, Rahmat; Adrianto, Fajri (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2024)
One of the causes of tax avoidance actions is influenced by corporate governance factors, including ownership structure. This study examines the relationship between institutional ownership structure and tax avoidance activities, with the moderating effect of independent directors. The research utilizes panel data from banking companies listed on the Indonesia Stock Exchange (IDX) from 2013 to 2022, totaling 430 firm-year observations. The estimation model employs Ordinary Least Square (OLS) approach. The results indicate that institutional ownership structure has a significant negative effect on tax avoidance actions. The moderating effect of independent directors does not have a significant influence on the relationship between institutional ownership structure and tax avoidance activities. Monitoring and internal control mechanisms are essential to mitigate actions detrimental to the interests of minority shareholders.